Oat growth under different nitrogen doses in eucalyptus alley cropping system in subtropical Brazil - Deiss, Leonardo; de Moraes, Anibal; Pelissari, Adelino; Neto, Francisco; Silva, Vanderley; Andreolla, Veruschka (Revista Ciência Agronômica, 2014)
Plant growth analysis was performed to determine how oat (Avena sativa L. cv. IPR 126) cultivated for grain responds to the eucalyptus (Eucalyptus dunnii Maiden) alley cropping system (ACS) in subtropical Brazil. The hypothesis of this work was that oat growth response is not modified by nitrogen at distances relative to 4 year old eucalyptus tracks in the ACS. The objective of this study was to determine how the oat growth was influenced by nitrogen doses (12 and 80 kg N ha-1) at five equidistant positions between two adjacent eucalyptus double line tracks [20 m (4 m x 3 m)] in ACS and traditional no-till farming. The experiment was conducted in a split-block randomized block design with four replicates. It was evaluated the oat relative growth rate, unit leaf rate, leaf weight fraction, panicle phytomass, panicle relative filling rate and grains-to-panicle ratio. Nitrogen doses altered the growth response differently in positions relative to the adjacent eucalyptus tracks; therefore, different nitrogen doses should be used in positions relative to the trees to improve oat growth in ACS in Subtropical Brazil.